Lithium ion battery positive electrode material and preparation method thereof

By adjusting the ratio of nickel, cobalt, manganese and introducing thermal stabilizing additives such as lithium phosphate and alumina, combining a composite of carbon nanotubes and graphene and a mixture of polyvinylidene fluoride and sodium carboxymethylcellulose, a high-performance lithium-ion battery cathode material was prepared, solving the shortcomings of existing materials in high-temperature performance and safety, and achieving a good balance of energy density, cost and safety.

CN119812302APending Publication Date: 2025-04-11ZHUZHOU SHENGHUA TECH CO LTD

Patent Information

Application Number
CN202510294603.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing lithium-ion battery positive electrode materials have shortcomings in high-temperature performance and safety, especially in the fields of electric vehicles and large-scale energy storage, where there are limitations on cost-sensitive application scenarios.

Method used

By adjusting the ratio of nickel, cobalt and manganese, and introducing lithium phosphate and alumina as thermal stabilizing additives, combining a composite of carbon nanotubes and graphene and a mixture of polyvinylidene fluoride and sodium carboxymethylcellulose, a high-performance lithium-ion battery cathode material was prepared.

Benefits of technology

A good balance between energy density, cost and safety is achieved, the energy density and thermal stability of the battery are improved, the cycle life is extended, and the risk of thermal runaway is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812302A_ABST
    Figure CN119812302A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery positive electrode material and a preparation method thereof, the lithium ion battery positive electrode material comprises an active substance, a conductive additive, a binder and a thermal stability additive, the active substance is # imgabs0 # with a layered structure, x + y + z = 1, 0.5 < = x < = 0.8, 0.1 < = y < = 0.3, 0.1 < = z < = 0.3, the conductive additive is a compound of a carbon nanotube and graphene, and the thermal stability additive is a mixture of a carbon nanotube and graphene. The binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the sum of the mass fraction of the lithium phosphate and the mass fraction of the aluminum oxide in the thermal stability additive is 0.5-10%, and the mass fraction of the lithium phosphate is 0.5-5%. According to the lithium ion battery positive electrode material and the preparation method thereof, the stability of the positive electrode material at high temperature can be improved, the thermal runaway risk is reduced, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, in particular to a lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] In today's society, lithium-ion batteries are widely used in portable electronic devices, electric vehicles, energy storage systems and other fields due to their advantages such as high energy density, long cycle life and no memory effect. As the requirements for battery performance in these application scenarios continue to increase, the development of high-performance lithium-ion battery positive electrode materials has become the core research direction. Early lithium-ion battery positive electrode materials were mainly lithium cobalt oxide, which has a high operating voltage and good cycle performance. However, the scarcity and high cost of cobalt resources limit its large-scale application, especially in cost-sensitive electric vehicles and large-scale energy storage fields. With the development of the battery industry, the research and development of lithium-ion battery positive electrode materials has gone through a development process from lithium cobalt oxide to ternary materials. In order to overcome the shortcomings of ternary materials in high temperature performance and safety, thermally stable additives and their modification technology have become the focus of current research.

[0003] Lithium phosphate can form a stable protective film on the surface of the positive electrode material, inhibiting the decomposition of the electrolyte and the side reactions between the positive electrode material and the electrolyte, thereby improving the thermal stability and cycle life of the battery. Aluminum oxide has high thermal stability and chemical stability, and can play an isolating and buffering role at high temperatures to prevent thermal diffusion and structural damage of the positive electrode material. From the fourth to the sixth embodiments, it can be seen that as the total amount of lithium phosphate and aluminum oxide added increases from 5% to 10%, the thermal decomposition starting temperature increases from 220°C to 230°C, and the battery thermal runaway temperature increases from 270°C to 280°C, which effectively proves the role of thermal stability additives in improving thermal stability. Through the study of active material composition, thermal stability additives and their modification methods, the performance of lithium-ion batteries is continuously improved to meet the growing market demand. Summary of the invention

[0004] To achieve the above objectives, the present invention is implemented by the following technical solutions: A lithium ion battery positive electrode material and a preparation method thereof, comprising an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and 0.5≤x≤0.8, 0.1≤y≤0.3, 0.1≤z≤0.3, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermally stable additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermally stable additive is 0.5% to 10%, wherein the mass fraction of lithium phosphate is 0.5% to 5%, and the mass fraction of aluminum oxide is 0% to 5%.

[0005] Preferably, the Ni, Co and Mn elements in the active material are uniformly distributed in the crystal structure, and the precursor is prepared by a co-precipitation method, and then calcined at a high temperature to form a stable layered structure.

[0006] Preferably, in the composite of carbon nanotubes and graphene, the mass ratio of carbon nanotubes to graphene is 1:1 to 3:1.

[0007] Preferably, in the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the mass ratio of polyvinylidene fluoride to sodium carboxymethyl cellulose is 2:1 to 4:1.

[0008] A method for preparing a positive electrode material for a lithium-ion battery comprises the following steps: Dissolve nickel salt, cobalt salt and manganese salt in deionized water according to a predetermined molar ratio to form a uniform metal salt solution with a concentration of 1 mol / L; Under stirring, a precipitant is slowly added dropwise to the metal salt solution, wherein the precipitant is a mixed solution of sodium hydroxide and ammonia water, and the volume ratio of sodium hydroxide to ammonia water is 2:1. At the same time, a complexing agent, citric acid, is added in an amount of 1% of the total mass of the metal salt. The reaction temperature is controlled to be 50°C, the pH value is 11-12, the stirring speed is 700 rpm, and the reaction time is 3 hours to obtain Precursor; The precursor was washed multiple times by centrifugation with deionized water for 4 times, and the centrifugal speed was 4000 rpm for 15 minutes after each washing, until the pH value of the washing solution was neutral, impurity ions were removed, and a pure precursor was obtained; The precursor and lithium carbonate or lithium hydroxide are uniformly mixed in a ball mill according to a stoichiometric ratio, the ball milling speed is 400 rpm, and the ball milling time is 3 hours to obtain a mixed material; calcining the mixture in air or oxygen atmosphere at 700-900° C. for 6-10 hours at a heating rate of 7° C. / min to obtain a primary positive electrode material; The heat-stabilizing additive was added to the primary positive electrode material and mixed in a planetary ball mill at a speed of 300 rpm for 2 hours; The doped material is calcined again at 300-600° C. for 3-5 hours in air or oxygen atmosphere at a heating rate of 5° C. / min to obtain the final lithium-ion battery positive electrode material; The final lithium-ion battery positive electrode material is mixed with the composite of carbon nanotubes and graphene and the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose according to a predetermined mass ratio, wherein the mass ratio of carbon nanotubes to graphene in the composite of carbon nanotubes and graphene is 2:1, and the mass ratio of polyvinylidene fluoride to sodium carboxymethyl cellulose in the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose is 3:1; The composite of carbon nanotubes and graphene is dispersed in N-methylpyrrolidone solvent, and ultrasonic dispersion is performed using an ultrasonic dispersion device with an ultrasonic power of 400 W and an ultrasonic time of 45 minutes to form a uniform conductive slurry; Add the final lithium-ion battery positive electrode material into the conductive slurry, stir at a speed of 1000 rpm for 2 hours, and stir evenly; Finally, a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose was added and stirring was continued at a speed of 800 rpm for 3 hours to form a final positive electrode material slurry, which can be coated on a current collector by a coating process to prepare a positive electrode for a lithium-ion battery.

[0009] Preferably, during the coprecipitation process, the metal salt solution is preheated to 30-40° C. before adding the precipitant.

[0010] Preferably, during the primary calcination and the secondary calcination, the material is placed at a specific position in the calcination furnace so that the material is heated evenly during the calcination process. The position is 10-20 cm away from the furnace wall.

[0011] Preferably, in the step of mixing the conductive agent and the binder, the formed positive electrode material slurry is filtered using a filter membrane with a pore size of 0.2-0.5 micrometers to remove undispersed large particles.

[0012] Preferably, the heat stabilizing additive may also be replaced by a modifying additive, and the preparation method of the modifying additive is as follows: Add an appropriate amount of lithium phosphate raw material and zirconia balls with a diameter of 1 mm into a ball mill with a ball-to-material ratio of 15:1, and ball mill for 15 hours at a speed of 400 rpm to obtain nano-scale lithium phosphate particles; Aluminum salt is dissolved in an organic solvent, and a proper amount of complexing agent and catalyst are added, and the mixture is stirred and reacted at 70°C for 4 hours to form a sol, and then aged, dried and calcined at 500°C for 3 hours to obtain nano-sized aluminum oxide particles; Take nano-sized lithium phosphate particles, add the nano-sized lithium phosphate particles into the organic silane coupling agent solution, and stir the reaction at 50° C. for 3 hours to make the organic silane coupling agent evenly coat the surface of the lithium phosphate particles; For nano-sized aluminum oxide particles, atomic layer deposition technology is used to deposit a 7-nanometer-thick titanium dioxide film on the surface of the aluminum oxide particles using trimethylaluminum and water as precursors; The surface-coated nano-scale lithium phosphate particles are mixed with an appropriate amount of magnesium salt, and calcined at 900°C for 4 hours under an argon protective atmosphere to uniformly dope the magnesium element into the lithium phosphate lattice. The doping amount of the magnesium element is 2% of the amount of the lithium phosphate substance. The surface-coated nano-alumina particles were mixed with a lanthanum salt solution, and stirred at 70°C for 5 hours to dope the lanthanum element into the alumina lattice. The doping amount of the lanthanum element was 1% of the amount of the alumina substance. The modified additive is obtained by mixing the element-doped nano-scale lithium phosphate particles with nano-scale aluminum oxide particles.

[0013] The present invention provides a lithium ion battery positive electrode material and a preparation method thereof. The present invention has the following beneficial effects: The lithium-ion battery positive electrode material and preparation method thereof can achieve a good balance between energy density, cost and safety by adjusting the ratio of nickel, cobalt and manganese in the ternary positive electrode material, thereby improving the battery energy density. The introduction of thermally stable additives such as lithium phosphate and aluminum oxide can improve the stability of the positive electrode material at high temperatures, reduce the risk of thermal runaway, and extend the battery cycle life. The thermally stable additives are modified by nano-sizing, surface coating and element doping to enhance their dispersibility and binding force with the positive electrode material. The research on the active material composition, thermally stable additives and their modification methods provides a direction for the continuous improvement of lithium-ion battery performance, which helps to meet the growing demand for high-performance batteries in portable electronic devices, electric vehicles, energy storage systems and other fields. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] In the first embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it includes an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.5, y=0.3, z=0.2, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermal stability additive is 0.5%, wherein the mass fraction of lithium phosphate is 0.5%, and the mass fraction of aluminum oxide is 0%; The preparation method of the positive electrode material of lithium-ion battery is as follows: Dissolve nickel salt, cobalt salt and manganese salt in deionized water according to a predetermined molar ratio to form a uniform metal salt solution with a concentration of 1 mol / L; Under stirring, a precipitant is slowly added dropwise to the metal salt solution, wherein the precipitant is a mixed solution of sodium hydroxide and ammonia water, and the volume ratio of sodium hydroxide to ammonia water is 2:1. At the same time, a complexing agent, citric acid, is added in an amount of 1% of the total mass of the metal salt. The reaction temperature is controlled to be 50°C, the pH value is 11-12, the stirring speed is 700 rpm, and the reaction time is 3 hours to obtain Precursor; The precursor was washed multiple times by centrifugation with deionized water for 4 times, and the centrifugal speed was 4000 rpm for 15 minutes after each washing, until the pH value of the washing solution was neutral, impurity ions were removed, and a pure precursor was obtained; The precursor and lithium carbonate are uniformly mixed in a ball mill according to a stoichiometric ratio, the ball milling speed is 400 rpm, and the ball milling time is 3 hours to obtain a mixed material; The mixed material is calcined at 900° C. for 10 hours in an air atmosphere at a heating rate of 7° C. / min to obtain a primary positive electrode material; The heat-stabilizing additive was added to the primary positive electrode material and mixed in a planetary ball mill at a speed of 300 rpm for 2 hours; The doped material was calcined again at 600° C. for 6 hours in an air atmosphere at a heating rate of 5° C. / min to obtain the final lithium-ion battery positive electrode material; The final lithium-ion battery positive electrode material is mixed with the composite of carbon nanotubes and graphene and the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose according to a predetermined mass ratio, wherein the mass ratio of carbon nanotubes to graphene in the composite of carbon nanotubes and graphene is 2:1, and the mass ratio of polyvinylidene fluoride to sodium carboxymethyl cellulose in the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose is 3:1; The composite of carbon nanotubes and graphene is dispersed in N-methylpyrrolidone solvent, and ultrasonic dispersion is performed using an ultrasonic dispersion device with an ultrasonic power of 400 W and an ultrasonic time of 45 minutes to form a uniform conductive slurry; Add the final lithium-ion battery positive electrode material into the conductive slurry, stir at a speed of 1000 rpm for 2 hours, and stir evenly; Finally, a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose was added and stirring was continued at a speed of 800 rpm for 3 hours to form a final positive electrode material slurry, which can be coated on a current collector by a coating process to prepare a positive electrode for a lithium-ion battery.

[0016] In the second embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it includes an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.6, y=0.2, z=0.2, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermal stability additive is 0.5%, wherein the mass fraction of lithium phosphate is 0.5%, and the mass fraction of aluminum oxide is 0%; The preparation method of the positive electrode material for lithium-ion batteries is the same as that of the first embodiment, wherein the calcination temperature during the preparation of the primary positive electrode material is adjusted to 850° C., and the atmosphere is an oxygen atmosphere.

[0017] In the third embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it includes an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.8, y=0.1, z=0.1, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermal stability additive is 0.5%, wherein the mass fraction of lithium phosphate is 0.5%, and the mass fraction of aluminum oxide is 0%; The preparation method of the positive electrode material of the lithium-ion battery is the same as that of the first embodiment, wherein the lithium source in the preparation of the primary positive electrode material is lithium hydroxide, the calcination temperature is adjusted to 780°C, the atmosphere is an oxygen atmosphere, and the atmosphere for secondary sintering of the doped material is an oxygen atmosphere.

[0018] In a fourth embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it comprises an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. Wherein x+y+z=1, and x=0.5, y=0.3, z=0.2, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermal stability additive is 5%, wherein the mass fraction of lithium phosphate is 2.5%, and the mass fraction of aluminum oxide is 2.5%; The method for preparing the positive electrode material of the lithium-ion battery is the same as that of the first embodiment.

[0019] In a fifth embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it comprises an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.6, y=0.2, z=0.2, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermal stability additive is 10%, wherein the mass fraction of lithium phosphate is 5%, and the mass fraction of aluminum oxide is 5%; The preparation method of the positive electrode material of the lithium-ion battery is the same as that of the second embodiment.

[0020] In the sixth embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it comprises an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.8, y=0.1, z=0.1, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermal stability additive is 10%, wherein the mass fraction of lithium phosphate is 5%, and the mass fraction of aluminum oxide is 5%; The method for preparing the positive electrode material of the lithium-ion battery is the same as that of the third embodiment.

[0021] In the seventh embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it includes an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.6, y=0.2, z=0.2, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the modified additive is 0.5%, wherein the mass fraction of lithium phosphate is 0.5%, and the mass fraction of aluminum oxide is 0%; The preparation method of the modified additive is as follows: Add lithium phosphate raw material and zirconia balls with a diameter of 1 mm into a ball mill with a ball-to-material ratio of 15:1, and mill at a speed of 400 rpm for 15 hours to obtain nano-scale lithium phosphate particles; Aluminum salt is dissolved in an organic solvent, and a proper amount of complexing agent and catalyst are added, and the mixture is stirred and reacted at 70°C for 4 hours to form a sol, and then aged, dried and calcined at 500°C for 3 hours to obtain nano-sized aluminum oxide particles; Take nano-sized lithium phosphate particles, add the nano-sized lithium phosphate particles into the organic silane coupling agent solution, and stir the reaction at 50° C. for 3 hours to make the organic silane coupling agent evenly coat the surface of the lithium phosphate particles; For nano-sized aluminum oxide particles, atomic layer deposition technology is used to deposit a 7-nanometer-thick titanium dioxide film on the surface of the aluminum oxide particles using trimethylaluminum and water as precursors; The surface-coated nano-scale lithium phosphate particles are mixed with an appropriate amount of magnesium salt, and calcined at 900°C for 4 hours under an argon protective atmosphere to uniformly dope the magnesium element into the lithium phosphate lattice. The doping amount of the magnesium element is 2% of the amount of the lithium phosphate substance. The surface-coated nano-alumina particles were mixed with a lanthanum salt solution, and stirred at 70°C for 5 hours to dope the lanthanum element into the alumina lattice. The doping amount of the lanthanum element was 1% of the amount of the alumina substance. The modified additive is obtained by mixing the element-doped nano-scale lithium phosphate particles with nano-scale aluminum oxide particles; The method for preparing the positive electrode material of the lithium-ion battery is the same as that of the second embodiment.

[0022] In the eighth embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it comprises an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.8, y=0.1, z=0.1, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the modified additive is 5%, wherein the mass fraction of lithium phosphate is 2.5%, and the mass fraction of aluminum oxide is 2.5%; The preparation method of the modified additive is the same as that of the seventh embodiment; The method for preparing the positive electrode material of the lithium-ion battery is the same as that of the third embodiment.

[0023] In the ninth embodiment, the present invention provides a technical solution: a positive electrode material for a lithium-ion battery, characterized in that it comprises an active substance, a conductive additive, a binder and a thermally stable additive, wherein the active substance is a layered structure. , wherein x+y+z=1, and x=0.6, y=0.2, z=0.2, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermal stability additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the modified additive is 10%, wherein the mass fraction of lithium phosphate is 5%, and the mass fraction of aluminum oxide is 5%; The preparation method of the modified additive is the same as that of the seventh embodiment; The preparation method of the positive electrode material of the lithium-ion battery is the same as that of the second embodiment.

[0024] Performance testing method: According to the preparation methods of each embodiment, sufficient lithium-ion battery positive electrode material samples are prepared, and the matching negative electrode materials, electrolytes, separators and other materials required for battery assembly are prepared; The prepared positive electrode material is mixed with a conductive agent and a binder in a certain ratio of 8:1:1, N-methylpyrrolidone solvent is added, and the mixture is stirred evenly to form a positive electrode slurry. The positive electrode slurry is evenly coated on an aluminum foil current collector, vacuum dried at 120°C, and then punched into circular pole pieces. Graphite is used as a negative electrode material, and the negative electrode piece is coated and dried on a copper foil. The positive electrode piece, the separator, and the negative electrode piece are stacked in sequence in an argon-filled glove box using a separator, and the electrolyte is injected to assemble a button battery. Use the battery testing system to perform charge and discharge tests on the assembled batteries, record the first charge capacity, first discharge capacity, charge and discharge efficiency and other data, perform multiple cycle charge and discharge tests under the same current density and voltage window, record the charge and discharge capacity of each cycle, and evaluate the battery capacity retention rate; Place an appropriate amount of positive electrode material sample into the DSC crucible, and under the protection of inert gas, raise the temperature from room temperature to a high temperature of 300°C at a rate of 10°C / min, determine the thermal decomposition temperature of the positive electrode material, the heat change during the thermal decomposition process and other parameters, evaluate the effect of thermal stability additives on the thermal stability of the positive electrode material, and perform accelerated calorimeter test: place the assembled battery into the ARC device, at an initial temperature of 50°C, monitor the temperature and pressure changes inside the battery, record the temperature at which the battery undergoes thermal runaway, the temperature rise rate during thermal runaway and other parameters, and evaluate the overall thermal stability of the battery.

[0025] The specific test data are as follows:

[0026] According to the above test results, the eighth embodiment is the best embodiment of the present invention.

[0027] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A positive electrode material for a lithium ion battery, characterized in that: The invention comprises an active material, a conductive additive, a binder and a thermally stable additive, wherein the active material is a layered structure. , wherein x+y+z=1, and 0.5≤x≤0.8, 0.1≤y≤0.3, 0.1≤z≤0.3, the conductive additive is a composite of carbon nanotubes and graphene, the binder is a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the thermally stable additive is a mixture of lithium phosphate and aluminum oxide, the total mass fraction of lithium phosphate and aluminum oxide in the thermally stable additive is 0.5% to 10%, wherein the mass fraction of lithium phosphate is 0.5% to 5%, and the mass fraction of aluminum oxide is 0% to 5%.

2. A lithium ion battery positive electrode material according to claim 1, characterized in that: The Ni, Co and Mn elements in the active material are uniformly distributed in the crystal structure, and the precursor is prepared by a co-precipitation method, and then calcined at a high temperature to form a stable layered structure.

3. A lithium-ion battery positive electrode material according to claim 1, characterized in that: In the composite of carbon nanotubes and graphene, the mass ratio of carbon nanotubes to graphene is 1:1 to 3:

1.

4. A lithium-ion battery positive electrode material according to claim 1, characterized in that: In the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose, the mass ratio of polyvinylidene fluoride to sodium carboxymethyl cellulose is 2:1 to 4:

1.

5. A method for preparing a positive electrode material for a lithium ion battery, characterized in that: The steps include: Dissolve nickel salt, cobalt salt and manganese salt in deionized water according to a predetermined molar ratio to form a uniform metal salt solution with a concentration of 1 mol / L; Under stirring, a precipitant is slowly added dropwise to the metal salt solution, wherein the precipitant is a mixed solution of sodium hydroxide and ammonia water, and the volume ratio of sodium hydroxide to ammonia water is 2:

1. At the same time, a complexing agent, citric acid, is added in an amount of 1% of the total mass of the metal salt. The reaction temperature is controlled to be 50°C, the pH value is 11-12, the stirring speed is 700 rpm, and the reaction time is 3 hours to obtain Precursor; The precursor was washed multiple times by centrifugation with deionized water for 4 times, and the centrifugal speed was 4000 rpm for 15 minutes after each washing, until the pH value of the washing solution was neutral, impurity ions were removed, and a pure precursor was obtained; The precursor and lithium carbonate or lithium hydroxide are uniformly mixed in a ball mill according to a stoichiometric ratio, the ball milling speed is 400 rpm, and the ball milling time is 3 hours to obtain a mixed material; calcining the mixture in air or oxygen atmosphere at 700-900° C. for 6-10 hours at a heating rate of 7° C. / min to obtain a primary positive electrode material; The heat-stabilizing additive was added to the primary positive electrode material and mixed in a planetary ball mill at a speed of 300 rpm for 2 hours; The doped material is calcined again at 300-600° C. for 3-5 hours in air or oxygen atmosphere at a heating rate of 5° C. / min to obtain the final lithium-ion battery positive electrode material; The final lithium-ion battery positive electrode material is mixed with the composite of carbon nanotubes and graphene and the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose according to a predetermined mass ratio, wherein the mass ratio of carbon nanotubes to graphene in the composite of carbon nanotubes and graphene is 2:1, and the mass ratio of polyvinylidene fluoride to sodium carboxymethyl cellulose in the mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose is 3:1; The composite of carbon nanotubes and graphene is dispersed in N-methylpyrrolidone solvent, and ultrasonic dispersion is performed using an ultrasonic dispersion device with an ultrasonic power of 400 W and an ultrasonic time of 45 minutes to form a uniform conductive slurry; Add the final lithium-ion battery positive electrode material into the conductive slurry, stir at a speed of 1000 rpm for 2 hours, and stir evenly; Finally, a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose was added and stirring was continued at a speed of 800 rpm for 3 hours to form a final positive electrode material slurry, which can be coated on a current collector by a coating process to prepare a positive electrode for a lithium-ion battery.

6. The method for preparing a positive electrode material for a lithium ion battery according to claim 5, characterized in that: During the coprecipitation process, the metal salt solution is preheated to 30-40° C. before adding the precipitant.

7. The method for preparing a positive electrode material for a lithium ion battery according to claim 5, characterized in that: During the primary calcination and secondary calcination processes, the materials are placed at a specific position in the calcination furnace so that the materials are heated evenly during the calcination process. The position is 10-20 cm away from the furnace wall.

8. The method for preparing a positive electrode material for a lithium ion battery according to claim 5, characterized in that: In the step of mixing the conductive and binder materials, the formed positive electrode material slurry is filtered using a filter membrane with a pore size of 0.2-0.5 microns to remove undispersed large particles.

9. The method for preparing a positive electrode material for a lithium ion battery according to claim 5, characterized in that: The thermal stabilizing additive may also be replaced by a modifying additive, and the preparation method of the modifying additive is as follows: Add an appropriate amount of lithium phosphate raw material and zirconia balls with a diameter of 1 mm into a ball mill, with a ball-to-material ratio of 15:1, and mill at a speed of 400 rpm for 15 hours to obtain nano-scale lithium phosphate particles; Aluminum salt is dissolved in an organic solvent, and a proper amount of complexing agent and catalyst are added, and the mixture is stirred and reacted at 70°C for 4 hours to form a sol, and then aged, dried and calcined at 500°C for 3 hours to obtain nano-sized aluminum oxide particles; Take nano-sized lithium phosphate particles, add the nano-sized lithium phosphate particles into the organic silane coupling agent solution, and stir the reaction at 50° C. for 3 hours to make the organic silane coupling agent evenly coat the surface of the lithium phosphate particles; For nano-sized aluminum oxide particles, atomic layer deposition technology is used to deposit a 7-nanometer-thick titanium dioxide film on the surface of the aluminum oxide particles using trimethylaluminum and water as precursors; The surface-coated nano-scale lithium phosphate particles are mixed with an appropriate amount of magnesium salt, and calcined at 900°C for 4 hours under an argon protective atmosphere to uniformly dope the magnesium element into the lithium phosphate lattice. The doping amount of the magnesium element is 2% of the amount of the lithium phosphate substance. The surface-coated nano-alumina particles were mixed with a lanthanum salt solution, and stirred at 70°C for 5 hours to dope the lanthanum element into the alumina lattice. The doping amount of the lanthanum element was 1% of the amount of the alumina substance. The modified additive is obtained by mixing the element-doped nano-scale lithium phosphate particles with the nano-scale aluminum oxide particles.

Citation Information

Patent Citations

  • Positive electrode material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    CN101145609A

  • Nickel-cobalt-aluminum-lithium ion battery positive material as well as preparation method and application thereof

    CN106654237A

  • Thermochemical blocking type composite positive electrode material, positive electrode plate and preparation method therefor, and lithium ion battery

    CN107146875A

  • Coated modified high-nickel ternary positive electrode material as well as preparation method and application thereof

    CN115425214A

Cited By

  • High-performance lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN120622450A

  • A high-performance lithium iron phosphate cathode material, a preparation method and application thereof

    CN120622450B

  • Dry-method material mixing process for lithium ion battery

    CN120727724A

  • Method for preparing cobalt-manganese composite precursor through coprecipitation

    CN121651448A